Sexual functioning and marital satisfaction among endometriosis patients in Malaysia: a cross-sectional study - Rao, Sharvina Ramesh; Sy-Cherng, Luke Woon; Hafizz, Abdul Muzhill Hannaan Abdul; Mamat @ Yusof, Mohd Nazzary; Shafiee, Mohamad Nasir (Frontiers in Psychology, 2023)
Endometriosis affects the sexual functioning and marital satisfaction of couples in a complex manner due to its clinical presentation of the disease. This study aimed to evaluate the prevalence of sexual dysfunction and marital disharmony among women with endometriosis beyond their diagnosis and treatment. A cross-sectional online survey was conducted among women with endometriosis in an endometriosis society at a Malaysian university hospital. Sociodemographic and clinical data were collected. Sexual function was measured using the Malay Version Female Sexual Function Index (MVFSFI), while marital satisfaction was evaluated with the Malay Version Golombok Rust Inventory for Marital Satisfaction (MVGRIMS). A total of 166 patients participated in this survey. The median age was 35 years (Interquartile range, IQR:32.00–39.25 years); 91.6% of participants were Malay. The median score of MVFSFI was 56.00 (IQR: 34.75–68.00). Most of the study subjects (n = 96) reported poor to very severe marital satisfaction problems, equivalent to MVGRIMS transformed score of more than 5. High levels of MVGRIMS scores have a moderately strong negative correlation with lower scores for most domains of the MVFSFI. In the stepwise multiple logistic regression, only MVFSFI total scores (p = 0.029), MVFSFI lubrication scores (p = 0.009), and MVFSFI satisfaction (p = 0.010) scores were significantly associated with poor marital satisfaction. Both sexual dysfunction and marital satisfactions commonly affect women with endometriosis and are closely interlinked. Targeted efforts should be made in multiple aspects to improve the quality of sexual functioning and marital satisfaction among endometriosis patients.